Distal‐to‐proximal delay for ablation of premature ventricular contractions. (27th December 2018) - Clementy, Nicolas; Ancedy, Yann; Bisson, Arnaud; Andre, Clémentine; Pierre, Bertrand; Fauchier, Laurent; Babuty, Dominique
Abstract: Introduction: Ablation of premature ventricular contractions (PVCs) has emerged as a safe and effective treatment in patients experiencing a high PVCs burden. Mapping of PVCs origin may sometimes be challenging. We sought to evaluate the accuracy of a new electrophysiological criterion, the distal‐to‐proximal (DP) delay, at localizing the optimal site for ablation of ventricular ectopic foci. Methods and Results: Consecutive patients with ablation attempts of symptomatic PVCs were included. Prematurity and DP delay—that is, the time duration between the onset of ablation catheter distal bipolar electrogram and the onset of proximal bipolar electrogram—were measured at successful and unsuccessful ablation sites by three blinded experienced electrophysiologists. Mean DP delay at effective ablation sites ( N  = 30) was significantly higher than at ineffective sites ( N  = 55) (23 ± 9 vs 11 ± 8 milliseconds; P  < 0.0001). DP delay had good‐to‐excellent interrater reliability. A DP delay greater than or equal to 15 milliseconds had the highest accuracy at predicting a successful ablation site (sensitivity 0.97, the area under receiver operating characteristic curve 0.87; P  < 0.0001). Conclusion: DP delay is an additional, simple, and effective electrophysiological parameter to accurately localize PVCs foci.